Radical-mediated dehydrative preparation of cyclic imides using (NH4)(2)S2O8-DMSO: application to the synthesis of vernakalant - Garad, Dnyaneshwar N.; Tanpure, Subhash D.; Mhaske, Santosh B. (Beilstein Journal of Organic Chemistry, 2015)
Ammonium persulfate-dimethyl sulfoxide (APS-DMSO) has been developed as an efficient and new dehydrating reagent for a convenient one-pot process for the synthesis of miscellaneous cyclic imides in high yields starting from readily available primary amines and cyclic anhydrides. A plausible radical mechanism involving DMSO has been proposed. The application of this facile one-pot imide forming process has been demonstrated for a practical synthesis of vernakalant.
Keywords: APS-DMSO; imides; practical synthesis; radical-mediated; vernakalant